An Insight into the Present Pandemic Scenario (COVID-19) with Respect to Maxfac Speciality - Arunima Awasthy; V Manjula; Liza Mohanty; Thousif Ahmed; H Aparna Latha; Jessica Y Jeevitha; Ramanpal S Makkad (Wolters Kluwer Medknow Publications, 2024)
The December 2019 pandemic killed about 2 million people and impacted countless more. SARS-CoV-2 causes COVID-19. The sickness causes dyspnea, high temperature, dry cough, loss of taste smell, etc., Due to the disease's fast spread, oral and maxillofacial surgical practices must be reconsidered. The World Health Organization, Association of Oral and Maxillofacial Surgeons of India, and other reputable bodies have released guidelines for safe and efficient COVID-19 therapy. This poll seeks surgeons' awareness of these worldwide and national bodies' guidance. A social media poll generated 173 replies, which were analyzed and interpreted. Many surgeons were aware of the recommendations and safety precautions, but others were unaware of the modifications in oral and maxillofacial surgery practice procedures.